Development of an enhanced recovery after surgery program for pediatric solid tumors - Mansfield, Sara A.; Kotagal, Meera; Hartman, Stephen; Murphy, Andrew J.; Davidoff, Andrew M.; Anghelescu, Doralina L.; Mecoli, Marc; Cost, Nicholas; Hogan, Brady; Rove, Kyle O. (Frontiers in Surgery, 2024)
Enhanced recovery after surgery (ERAS) is an evidence-based, multi-modal approach to decrease surgical stress, expedite recovery, and improve postoperative outcomes. ERAS is increasingly being utilized in pediatric surgery. Its applicability to pediatric patients undergoing abdominal tumor resections remains unknown.A group of key stakeholders adopted ERAS principles and developed a protocol suitable for the variable complexity of pediatric abdominal solid tumor resections. A multi-center, prospective, propensity-matched case control study was then developed to evaluate the feasibility of the protocol. A pilot-phase was utilized prior to enrollment of all patients older than one month of age undergoing any abdominal, retroperitoneal, or pelvic tumor resections. The primary outcome was 90-day complications per patient. Additional secondary outcomes included: ERAS protocol adherence, length of stay, time to administration of adjuvant chemotherapy, readmissions, reoperations, emergency room visits, pain scores, opioid usage, and differences in Quality of Recovery 9 scores.Institutional review board approval was obtained at all participating centers. Informed consent was obtained from each participating patient. The results of this study will be presented at pertinent society meetings and published in peer-reviewed journals. We expect the results will inform perioperative care for pediatric surgical oncology patients and provide guidance on initiation of ERAS programs. We anticipate this study will take four years to meet accrual targets and complete followup.